Community-based climate adaption: A perspective on the interface between a common pool resource system and an individual-based market transaction system - Yingjun Qi; Gongbuzeren; Wenjun Li (Ecological Economics, 2023)
Because of land privatisation and marketisation in rural areas, community-based adaptation to climate change may face new challenges. A field survey conducted on the Qinghai–Tibetan Plateau (QTP) shows that herders with a grassland collective management system (CMS) suffer higher livestock mortality than those with an <a class="topic-link" href="https://www.sciencedirect.com/topics/economics-econometrics-and-finance/individuals-management" title="Learn more about individual management from ScienceDirect's AI-generated Topic Pages">individual management system (IMS) during the same extreme climatic events, in contrast to previous research findings. This study seeks to explain this contrast. The results show that although local herders have begun to rely on market-related adaptation strategies to cope with climate change, IMS herders are more inclined to rent-in grassland, while CMS herders are more inclined to purchase fodder. The high-cost grassland renting-in strategy reduces livestock mortality and total household economic loss more effectively than purchasing fodder during snow disasters. An important reason for this is that IMS strengthens market concepts and promotes interaction between herders and external markets, especially the grassland rental market, while CMS continues past grazing traditions and maintains traditional social relationships and collective concepts within the community. CMS herders fail to rent-in grassland due to psychological free-riding incentives and scale mismatch. In the face of repeated climatic disasters, however, CMS herders have also begun to overcome various obstacles to entering the grassland rental market through self-organization and are gradually forming a new pathway of adaptation to climate change.